Ethno-Design-Based Learning Tools to Enhance Students' Future Thinking - Putu Okta Satriani; I Wayan Widiana; I Wayan Ardana (Universitas Pendidikan Ganesha, 2026)
The ability to think about the future is one of the important 21st century competencies that needs to be developed in elementary school students to face dynamic global challenges. However, the implementation of learning in elementary schools still tends to use conventional media and has not integrated interactive technology and local wisdom optimally. This research aims to develop and test the effectiveness of ethno design-based learning tools assisted by Augmented Reality (AR) in improving elementary school students' future thinking abilities. This research is development research using the ADDIE model involving fifth grade elementary school students as research subjects. Data collection was carried out through observation, interviews, questionnaires and tests with instruments in the form of expert validation sheets, teacher and student response questionnaires, as well as future thinking ability test questions. Data were analyzed using quantitative descriptive analysis and Paired Sample T-Test. The products developed include AR media